Developing Geomorphologic Tourism in the Valleys of the Eastern Coast of the Dead Sea - BAZAZO, Ibrahim Kahlil; ALANANZEH, Omar Abedalla (Journal of Environmental Management and Tourism; Vol 11 No 6 (2020): JEMT Volume XI, Issue 6(46) Fall 2020, 2020)
The study aims to identify the pattern of geomorphologic tourism in the valleys of the eastern coast of the Dead Sea and the mechanisms for developing this type of tourism. An analysis of space visuals data and topographic maps were utilized to provide a holistic picture of the geomorphologic reality and the spatial relationships between tourism uses and the nature of this area. Relying on geographic information systems and remote sensing software, the study provides a holistic picture that contributes to the identification of the geomorphologic tourism pattern, and the future forecast in the form of spatial space within a holistic integrated approach based on scientific foundations. The study revealed the importance of the area with its great potentials represented in geomorphologic and biological diversity. It contributed to providing a comprehensive spatial database beneficial for decision-makers in adopting a comprehensive planning process for the study area.